If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = x + -1 Reorder the terms: 1 = -1 + x Solving 1 = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -1x = -1 + x + -1x Combine like terms: x + -1x = 0 1 + -1x = -1 + 0 1 + -1x = -1 Add '-1' to each side of the equation. 1 + -1 + -1x = -1 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -1 + -1 -1x = -1 + -1 Combine like terms: -1 + -1 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 6r^3+15r^2-6r= | | 6y^2+3y-18=0 | | -10+8k=3k-5 | | 2x+4(0)=8 | | x=4x+12 | | 8-2(x+5)=4(2x-1) | | 5x-1=4x+9 | | 8(5n+7)=216 | | 4=p-2 | | -5+x=-3 | | 16=4a+8+4a | | 6x+4=2(x-6) | | 8a^2-4d=60 | | 15x-7x=-52-5x | | 12x^2-33x+18=0 | | 8y^2+26y=-15 | | 5m+1-8m=22 | | 1m/9+10=16 | | M+4=20+3m | | 10x-35=5x+25 | | 3(4k+8)-2(2k+3)-14k= | | 8(y-5)=6y-19 | | 3x-9=x+15 | | 67*2(56+6)-(-7+7)= | | -7x+4x+15-8x= | | 6x-177=96-7x | | 6x+8=2x+24 | | P-15=-12 | | a^9+2a^8b-3a^7b^2=0 | | -30-7x=-11x+66 | | 3x-2=x+14 | | 8(6+r)=40 |